Development Derailed: Calgary and the CPR, 1962-64 - Max Foran (Athabasca University Press, 2013)
Development Derailed unravels a fascinating story of how politics undermined promise. The text outlines a proposal put forth in 1962 to develop the lands held by the Canadian Pacific Railway in downtown Calgary. Greeted with excitement and visions of enhanced tax revenues, increased land values, and new investment opportunities the plans ultimately fell prey to conflict between corporate rigidity and an unorganized, ill-informed civic administration and city council. Drawing on the private records of Rod Sykes, the CPR's onsite negotiator and later Calgary's mayor, Max Foran unravels the fascinating story of how politics undermined promise.